Simulation for senior undergraduate education of robot engineering based on Webots. Issue 5 (29th December 2020) - Yue, Haosong; Miao, Jinyu; Zhang, Jinqing; Fan, Changbo; Xu, Dong
Abstract: In this paper, a comprehensive simulation framework is presented for senior undergraduates of robot engineering based on open‐source simulation software, Webots. In our curriculum, a virtual quadruped robot is used to test different theories. First, students should design the physical structure of the robot and select proper drivers according to the requirements on its motion ability. Then, the kinematics and workspace of each leg should be analyzed. To overcome different terrains, terrain recognition, and motion planning methods are presented. Finally, the processes of building a virtual robot and its test environment are introduced. Simulation results demonstrate that it is possible to test different robot techniques in our proposed simulation framework. Teaching practice and feedback from students show their promotion of understanding of robot theories. Their interest in robots are also increased.